The Use of Key Risk Indicators in Operational Risk Management in Banks - Thlon, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Operational risk is defined as the possibility of losses resulting from the failure, deficiency or inadequacy of internal processes, people and systems or from external events. Operational risk measurement methods are different from techniques applicable to other types of risk. The particular issues involved in operational risk and the difficulty of estimating its impact on the level of income earned significantly complicate the measurement. Therefore, in order to estimate the level of operational risk there is a tendency to take a comprehensive approach to operational risk management, understood as the combination of qualitative risk estimation, quantitative measurement methods and Key Risk Indicators (KRI). The main objective of the paper is to analyse the most important aspects of the use of KRI in managing operational risk. This objective determines the paper’s structure. I analyse the definition, characteristics, applications and quantification methods of KRI, in that order.